Karakteristik Refrigeran Musicool Dalam Mesin Refrigerasi Kompresi Uap Menggunakan Evaporator Ganda - Purnomo, Bagiyo Condro; Widodo, Noto; Munahar, Suroto; Nugroho, Dimas (Universitas Muhammadiyah Yogyakarta, 2020)
Musicool is an alternative refrigerant developed as a working fluid in a steam compression refrigeration system. Musicool has many advantages compared to conventional refrigerants, the advantage is that it is environmentally friendly. This study aims to determine the characteristics of musicool 134 on a steam compression refrigeration machine using a double evaporator. The test is done by comparing the characteristics of a single evaporator refrigeration machine and a double evaporator using musicool 134. The research variable is the air flow through the evaporator that is equal to 0.022 kg / s, 0.027 kg / s, 0.033 kg / s. The test data is taken by measuring the temperature and pressure of each component in the refrigeration machine, then using the P-h diagram musicool 134, to determine the performance of the refrigeration machine. The results of the study provide information that the use of a double evaporator will give rise to an improved refrigeration system performance compared to using a single evaporator.